A decentralized blockchain-based model to secure confidential medical information - Chowdhury, Tahmid; Jahan, Tabassum Nusrat; Rifat, Golam Rabbani; Nahid, Sadman Sakib (Brac University, 2024)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2023.